Exploring local adjuvant antibiotics as viable alternative to systemic antibiotics in non-surgical periodontal therapy: Clinical, immunological and microbiological insights - Iva Milinkovic; Marija Vuckovic; Nadja Nikolic; Jelena Carkic; Zoran Aleksic; Sasha Jankovic; Jelena Milasin; Ana Djinic Krasavcevic (PLoS ONE, 2025)
Objectives The primary aim of the present study was to compare the reduction in periodontal probing depth after the use of either local or systemic adjuvant antibiotics during non-surgical periodontal therapy at baseline and the six-month follow-up. Secondary aims were to compare other clinical outcomes, total bacterial count, and relative expression levels of certain pro-inflammatory mediators following the use of locally and systemically delivered adjuvant antibiotics during the initial non-surgical periodontal therapy (NSPT). Material and methods A total of 38 periodontitis stage III grade B or C patients were randomly and equally assigned to receive either local (LA) (tazobactam + piperacillin preparation) or systemic antibiotics (SA) (amoxicillin and metronidazole combination) during NSPT. Clinical periodontal parameters (periodontal probing depth, clinical attachment level, bleeding on probing, and plaque index), and microbiological and immunological parameters: total bacterial count, and relative expression levels of IL-17 and TNF-α were evaluated at baseline and six months after NSPT. Results Both LA and SA significantly improved all clinical parameters after six months (p<0.001 for all comparisons). While a significant decrease of total bacterial count was observed after LA (p=0.001) and SA treatment (p=0.013), the insignificant differences between the two groups were observed after the sixth-month follow-up (p>0.05). Conversely, relative gene expression levels of IL-17 and TNF-α did not differ significantly between LA and SA six months after the NSPT. The insignificant differences between these cytokines’ relative levels were observed in both SA and LA between baseline and follow-up measurements. Conclusions The adjuvant use of piperacillin + tazobactam led to the comparable improvement of clinical, microbiological and immunological parameters to the conventional use of amoxicillin and metronidazol combination six months following the initial therapy of periodontitis. Therefore, these locally delivered antibiotics might be a promising alternative to the standard use of systemic amoxicillin and metronidazol combination during initial therapy of stage III periodontitis.